Social indicators and other income statistics using the EUROMOD baselin: A comparison with Eurostat and national statistics - Daniela Mantovani; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2003)
This paper reports an exercise to validate EUROMOD output for 1998 by comparing income statistics calculated from the baseline micro-output with comparable statistics from other sources, including the European Community Household Panel. The main potential reasons for discrepancies are identified. While there are some specific national issues that arise, there are two main general points to consider in interpreting EUROMOD estimates of social indicators across EU member States: (a) the method of updating microdata to 1998 and (b) the non takeup of means-tested benefits. A further conclusion is that comparisons of the type made in this paper are rarely definitive. The findings presented here should be treated as indicative of the reliability of the EUROMOD baseline as a starting point for policy simulations.
Keywords: C81; D31; I32; 330; European Union; Microsimulation; Poverty statistics; Income inequality